Sex sub analysis from observational multicenter registry of patients treated with Impella mechanical circulatory support device in Italy: the IMP-IT women. (25th November 2020) - Ziviello, F; Burzotta, F; Briguori, C; Trani, C; Nicolini, E; Masiero, G; Pagnotta, P; Pazzanese, V; Scandroglio, M; Piva, T; De Marco, F; Di Biasi, M; et al.
Abstract: Background: Women-specific data on safety, effectiveness, and outcomes for mechanical support in the setting of cardiogenic shock (CS) and high-risk percutaneous coronary intervention (HR-PCI) are still unsettled. The IMP-IT study was a multicenter observational national registry that enrolled all patients treated with Impella 2.5, Impella CP, Impella 5.0 and Impella RP, both for CS and HR-PCI indications, across 17 Italian centers from 2004 to June 2018 Purpose: To analyze the characteristics of female population enrolled in IMP-IT registry and to assess differences in presentation, timing to interventions and outcomes between men and women. Methods: The Women-IMP-IT study is a multicenter observational national registry focusing on female population enrolled in IMP-IT study. Baseline, procedural and hemodynamics characteristics, such as outcome were collected. Differences between men and women were examined. Results: Mean age of female population was 66.9±16.1 years, Body mass index was 26.3±5.5 kg/m 2 . There was a higher rate of cardiogenic shock (66.7% vs. 49.1%; p=0.06), NSTEMI (18% vs 9%, p=0.03) and acute myocarditis (9.6% vs 1.4%, p=0.01) in women vs men, associated with a lower rate of protected PCI (33.3% vs 50.9%, p=0.06). We did not observed a statistically difference in device related complications (27.4% vs 23.3%; p=0.50), respectively in women compared to men. In particular, no differences were observed in access site bleedings (10.8% vs 9%; p=0.70) and life threatening or severe bleeding (15.3% vs 11.4%; p=0.40). At one year, all-cause death rate was 45.1% in women vs 30.1% in men (p=0.016), and cardiac death rate was 42.5% in women and 27.5% in men (p=0.013). At 1-year no significant difference was observed in the rate of myocardial infarction (3.7% vs 2.3%; p=0.44), stroke (3.7% vs 2.6%; p=0.70), heat-failure hospitalization (7.7% vs 7.5%; p=1.0), need for left ventricular assist device or heart transplantation (1.3% vs 5.5%; p=0.21). Conclusions: In our series, use of Impella is CS and HR-PCI is increasing in female population. Sex-differences in mortality are mostly explained by clinical differences at presentation. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): EAPCI Education and Training Grants